ID: 31. Issue 1 (November 2015) - Bedsaul, Jacquelyn; Zaritsky, Luna; Zoon, Kathryn
<x xml:space="preserve">Abstract</x> Type I interferon (IFN) is one of the body's first line of defense against invading pathogens. The IFN-<alternatives><inline-graphic xlink:href="ark:/27927/pgj2n6x7qx7" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />α</alternatives> subgroup in the type I IFN family consists of 12 different proteins that are known to have antiviral properties. However, the specific functions, efficacies, and induction patterns of each IFN-<alternatives><inline-graphic xlink:href="ark:/27927/pgj2n6x7qx7" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />α</alternatives> subtype in response to viral pathogens have not been fully assessed. This study examines these properties using two RNA viruses, Sendai virus (SeV) and encephalomyocarditis virus (EMCV) and two human cell lines. Using the human lung epithelial cell line A549 and monocytoid cell line U937 we show that IFN-<alternatives><inline-graphic xlink:href="ark:/27927/pgj2n6x7qx7" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />α</alternatives> subtypes are unique in their antiviral properties. IFN-<alternatives><inline-graphic xlink:href="ark:/27927/pgj2n6x7qx7" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />α</alternatives> subtype pretreatment of both cell lines challenged with EMCV results in a range of antiviral activities. Subtype pretreatment followed by SeV challenge, however, did not protect either cell type. A549 cells were shown to induce very little type I IFN RNA upon SeV infection, but this induction results in the upregulation of IFN stimulated genes and biologically active IFN protein. Together, our study shows that IFN-<alternatives><inline-graphic xlink:href="ark:/27927/pgj2n6x7qx7" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />α</alternatives>s have cell type and virus specific functions. The inability of type I IFN to protect against SeV infection must be further explored mechanistically to uncover why biologically active type I IFN is unable to induce an antiviral state.